Useful Biodiversity Data Were Obtained by Novice Observers Using iNaturalist During College Orientation Retreats. (1st December 2021) - Stevenson, Robert; Merrill, Carl; Burn, Peter
Citizen scientist platforms such as eBird and iNaturalist are dramatically increasing the biodiversity data available for scientific research. Questions remain about the validity of data collected by people with undefined credentials. However, few studies have examined the data quality of citizen science studies in detail. As part of an autumn orientation program, the Honors College at UMass Boston invited incoming students for a retreat on Thompson Island in Boston Harbor Islands National and State Park. One of their activities was a three-hour bioblitz using iNaturalist. We reviewed data collected from three autumn orientations (2017–2019) to evaluate the quality of the data and to examine the hypothesis that first-time users can contribute useful biodiversity observations. The students collected more than 2, 000 observations and uploaded more than 5, 700 photographs, mostly of plants (about 50%) and animals (40%). Approximately 50% of the observations became Research Grade by iNaturalist criteria. Errors in GPS data (ca 1–4%) did not always place observations automatically in the project. First-time users, presumably because they are digital natives and have experience with cell phone cameras, quickly master the basics of iNaturalist. We conclude that students using the iNaturalist platform, with a crowd-sourced ID process, produce data that are useful for a variety of biodiversity studies.